Front Matter - School of Law, University of Pittsburgh (Journal of Law and Commerce, 2019)
NOTICE TO CONTRIBUTORS 1. The Journal invites the submission of unsolicited manuscripts. Submissions and correspondence concerning publications should be addressed to Editor-in-Chief, Journal of Law and Commerce, University of Pittsburgh School of Law, Barco Law Building, 3900 Forbes Avenue, Pittsburgh, PA 15260. 2. The Journal requests that manuscripts be accompanied by an abstract of not more than 200 words describing the contents of the article. 3. Footnotes should conform to The Bluebook: A Uniform System of Citation (20th ed. 2015). 4. All manuscripts, including footnotes and abstracts, should be typed and submitted directly to the website. Published twice yearly: Fall, Spring Annual Subscription Rate: U.S. ‑ $20.00; Foreign ‑ $25.00 Internet Address: http://jlc.law.pitt.edu/ E-mail Address: jlc.law@mail.pitt.edu Single copies of Volume 36 are $11.00 and may be ordered from the Business Manager, Journal of Law and Commerce, University of Pittsburgh School of Law, Barco Law Building, 3900 Forbes Avenue, Pittsburgh, PA 15260. Volumes 1 through 35 may be ordered from William S. Hein & Co., Inc., 1285 Main Street, Buffalo, NY 14209; (800) 828-7571. If subscription is to be discontinued at expiration, notice to that effect should be sent to the Journal office, otherwise it will be renewed.